A conceptual design study of generating locally-round beam in a diffraction-limited storage ring using skew quadrupole triplets - Du, Chongchong; Wang, Jiuqing; Ji, Daheng; Tian, Saike (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2021)
Diffraction-limited storage rings (DLSRs), with sub-100pm⋅rad electron emittances approaching the diffraction limit for hard X-rays, would provide unprecedented transverse coherence and much higher brightness than currently operational light sources to the synchrotron radiation scientific community. Instead of typical flat beam, some individual synchrotron light users prefer round beam, a beam with equivalent emittances between the horizontal and vertical planes, for the reasons of fully transverse coherent X-ray radiation and better photon–electron phase space match, and so on. To meet the requirements of different experimenters, obtaining a locally-round beam will be a significant subject in DLSR studies. We investigate the approaches of realizing locally-round beam in a storage ring, by means of a local emittance equalization of the transverse planes. In this paper, a novel method is proposed to achieve locally-round beam, performed with a combination of skew quadrupoles in insertion section of the storage ring. Theoretical analysis and application of this method to achieve a locally-round beam at DLSRs, particularly to High Energy Photon Source (HEPS) storage ring, are presented.